EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP MOTIVASI BELAJAR SISWA KELAS XI - Lona, Urai; Utomo, Bambang Budi; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to find out the effectiveness of snowball throwing teaching model in teaching Civic Education at SMA Muhammadiyah 1 Pontianak on the motivation of eleventh-grade learners. The technique used in this research was quasi-experimental with a model of a nonequivalent control group design. 33 XI IPS 2 learners were in the control group, while 30 XI IPS 3 learners were in the experimental group. The findings of the study show a variety between the experimental and control groups in the motivation of the learners. The average learning motivation of the control group applying the conventional learning model at two meetings was 62.43 per cent, while the experimental group using the applied learning model had a higher average of 77.45 per cent. Based on the 0.66 per centÂ effect size of the categorized medium, it has been shown that the applied learning model is effective for use inÂ class XI IPS 3. The Snowball Throwing learning model influences the motivation of students in class XI IPS 3 to learn Civic Education at SMA Muhammadiyah 1 Pontianak.Â Keywords: Effectiveness, Snowball Throwing Learning Model, Learning Motivation